2019
DOI: 10.1007/s00271-019-00654-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a combined filtration system and drip irrigation laterals on quality of rainbow trout farm effluent

Abstract: The main aim of this study was to investigate the qualitative changes of the rainbow trout effluent as water supply in a drip irrigation system. Two drip irrigation systems with a hydrocyclone filter, sand filter and screen filter for using freshwater (control treatment) and fish farm effluent were tested in Kurdistan province (northwest of Iran) in 2017. In addition, the effect of lateral drainage at the end of each irrigation event was also studied. Two emitter types with different discharge flows were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This operation time can be acceptable for T1 and T2 treatments but is too short for T3 treatment. Manbari et al (2020) reported a minimal head loss in a sand filter (with 3–5 mm and 5–8 mm grain sizes) in the treatment of rainbow trout effluent. In the present study, however, the sand sizes were smaller (0.8–1.2 mm and 2–3.5 mm), and consequently pressure loss and solids removal were higher, as has been previously reported (Duran‐Ros et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This operation time can be acceptable for T1 and T2 treatments but is too short for T3 treatment. Manbari et al (2020) reported a minimal head loss in a sand filter (with 3–5 mm and 5–8 mm grain sizes) in the treatment of rainbow trout effluent. In the present study, however, the sand sizes were smaller (0.8–1.2 mm and 2–3.5 mm), and consequently pressure loss and solids removal were higher, as has been previously reported (Duran‐Ros et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In the present experiment, solids removal efficiencies with the sand and disc filter (65%–68%) and trout fish effluent were between those values previously observed with urban effluents. Manbari et al (2020) observed suspended solids removal efficiencies for a screen filter placed after a sand filter of 23% and 43% with fresh water and trout fish farm effluent, respectively. In the present work, with a smaller grain size, the efficiencies increased considerably.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These varied performances may be attributed to differences in the type of wastewater or the level of treatment. It was shown that in using the e uent of multi-stage farms of rainbow trout, the screen lter (125-149 µm) performed better than the sand lter (grain size 3-5 and 5-8 mm) (Manbari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%